A Tripartite Knowledge Translation Program: Innovative Patient-Centered Approach to Clinical Research Participation for Individuals with Multiple Sclerosis. (17th July 2021) - Saini, Aman; Cochran, Colleen; Zucker-Levin, Audrey; Donkers, Sarah J.; Kumar, Pawan; Knox, Katherine B.; MacPherson, Jessica; Salapa, Hannah; Levin, Michael C.
Abstract : Background . Knowledge translation (KT) models that represent an individual's perspective are a sign of effective KT. Some common challenges in KT include participant engagement, organization of the team, and time demands of the participants. We implemented a unique tripartite KT program to (1) share current research, (2) inform persons living with multiple sclerosis (pwMS) about the clinical research process, and (3) invite pwMS to immediately participate in clinical research. The primary aim was to determine participants' perspectives on the value and acceptability of an experiential research program offered at a patient and family educational conference. Methods . A team of researchers identified factors that would impact the logistics of hosting an experiential research program at a conference and designed a unique tripartite KT program. The local multiple sclerosis (MS) society was engaged to select an appropriate location and invite stakeholders to the conference. A survey to determine participants' perspectives on the value and acceptability of the experiential research program was developed and analyzed. Results . 65 pwMS attended the conference, and 44 (67.7%) participated in the on-site experiential research program. 72.7% of the participants completed the survey, of which 93.8% stated that they strongly agree or agree with the following statements: "Did you feel like participating in research today was a valuable experience to you?" and "Did you feel like you were contributing to MS research?" 100% of the participants agreed or strongly agreed when asked "would you like to see more research activities taking place at these kinds of events?" Conclusions . This paper describes the logistics and challenges of conducting an experiential KT program, which proved to be rewarding for pwMS. The majority of pwMS attending the conference agreed to participate in the on-site experiential research program and an overwhelming majority of participants felt the experience was valuable.